Inter-ray variation in metatarsal strength properties in humans and African apes: Implications for inferring bipedal biomechanics in the Olduvai Hominid 8 foot. Issue 121 (August 2018) - Patel, Biren A.; Jashashvili, Tea; Bui, Stephanie H.; Carlson, Kristian J.; Griffin, Nicole L.; Wallace, Ian J.; Orr, Caley M.; Susman, Randall L.
Abstract: When measured as a ratio of mean midshaft diameter to bone length, the OH 8 fossil hominin foot exhibits a metatarsal (Mt) robusticity pattern of 1 > 5 > 3 > 4 > 2, which differs from the widely perceived "common" modern human pattern (1 > 5 > 4 > 3 > 2); African apes generally exhibit a third pattern (1 > 2 > 3 > 4 > 5). Largely because of the relative ranking of Mt2 and Mt5, OH 8 metatarsals structurally resemble the pattern exhibited by bipedal humans more than the pattern of quadrupedal and climbing African apes. Considering only these three phenotypes, however, discounts the potentially important functional implications of variation in modern human (and African ape) metatarsal robusticity patterns, suggesting that they are not useful for interpreting the specific biomechanics of a bipedal gait in fossils (i.e., whether it was modern human-like or not). Using computed tomography scans to quantify metatarsal midshaft cross-sectional geometry in a large sample of Homo (n=130), Gorilla (n=44) and Pan (n=80), we documented greater variation in metatarsal robusticity patterns than previously recognized in all three groups. While apes consistently show a 1 > 2 > 3 > 4 > 5 pattern in our larger sample, there does not appear to be a similarly precise single "common" human pattern. Rather, human metatarsals converge towards a 1 > 4/5 > 2/3 pattern, where metatarsals 4 and 5, and metatarsals 2 and 3, often "flip" positions relative to each other depending on the variable examined. After reassessing what a "common" human pattern could be based on a larger sample, the previously described OH 8 pattern of 1 > 5 > 3 > 4 > 2 is only observed in some humans (<6%) and almost never in apes (<0.5%). Although this suggests an overall greater similarity to (some) humans than to any ape in loading of the foot, the relatively rare frequency of these humans in our sample underscores potential differences in loading experienced by the medial and lateral columns of the OH 8 foot compared to modern humans.